KORELASI ANTARA KETERAMPILAN METAKOGNISI DENGAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KIMIA KELAS X MIA SMA NEGERI 7 PONTIANAK - Nurul Fitri; Mawardi Mawardi; Rizmahardian Azhari Kurniawan (Jurnal Ilmiah Ar-Razi, 2017)
ABSTRACTLow learning outcomes and lack of student activity on chemistry subject at X grade science students in SMAN 7 Pontianak was caused by low metacognition skills. Therefore, this research aimed to describe student‟s metacognition skills, learning activities, and learning outcomes in chemical subjects, as well as to determine the level of correlation among those variables. The method was descriptive method with correlational research. Students‟ metacognition skills were measured using MCAI questionnaire, students‟ learning outcomes by summative test documentation, and students‟ learning activities by learning activities questionnaires. The analysis showed that students‟ metacognition skill average was 79% in the developing category, which meant students can be helped toward realizing think if intrigued or supported, students‟ learning activities ware at the high category (51%), while students‟ learning outcomes was in the less category ( 38%). The correlation test (Pearson product moment test) results of students‟ metacognition skills with students‟ activity showed positive and significant correlation. Pearson correlation coefficient (r) was 0.542 as the moderate category and determination coefficient was 0.293. The correlation test results of students‟ metacognition skills with students‟ learning outcomes indicated that there was no correlation with the significant value of 0.136. Keywords: learning activities, metacognition skills, correlation, learning outcomes